Antipsychotic Augmentation Strategies to Ameliorate Negative and Cognitive Symptoms in Schizophrenia; Implications for Future Research - Duisterwinkel, Gerben; Bosker, F. J.; Scholte-Stalenhoef, A. N.; Vervoort, M.; Knegtering, H. (Central Nervous System Agents in Medicinal Chemistry, 2008)
Negative and cognitive symptoms of schizophrenia remain difficult to treat. Many add-on medications to alleviate these symptoms have been proposed and investigated. In this inventory the various treatment strategies published since 1990 are being reviewed and categorised according to the pharmacological mechanism putatively involved. Notwithstanding the problems one experiences when comparing the applied measures for negative and cognitive symptoms, three clear recommendations for future research can be made viz. modulation of glutamatergic systems, blockade of serotonin 5-HT2 receptors and modulation of histaminergic systems. Strategies aimed at nAChR subtypes may also hold some promise.
Keywords: negative symptoms